The Relation of Google Classroom Usage on Student’s Learning Outcomes for Elementary School Students - Firly Divariyani; Slameto Slameto (Universitas Pendidikan Ganesha, 2022)
The Covid-19 pandemic has caused various changes in the education system in Indonesia, especially in the use of online learning methods. However, implementing new technologies is challenging, especially for parents and teachers of lower-grade elementary school students. One form of technology that is applied in online learning is Google Classroom. This study aims to analyze the relationship between using Google Classroom during the Covid-19 pandemic and its effect on the learning process and outcomes. This study used qualitative research methods. The subjects of this study were 33 parents of students. Data was collected through surveys and interviews with parents and teachers. The data were analyzed qualitatively through the Technology Acceptance Model. The analysis results show that although the applied technology is well received, there is a difference between the scores and the results of evaluating student performance in face-to-face meetings with the teacher. Learning loss can be caused by parents who are too involved in the online learning process and teachers' difficulty adequately assessing student performance. The implication is that online education methods are ineffective and may have caused damage to the education system in general.